DOI: 10.2298/bg20121227jankovictomanic
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and food quality on variability of fitness components and physiology of digestion in the gypsy moth larvae Lymantria dispar L.

Abstract: Belgrade, 2012 REZIMETemperatura i kvalitet hrane utiču na performansu larvi gubara, Lymantria dispar L. nezavisno ili u međusobnoj interakciji. Strategije preživljavanja larvi gubara u temperaturno kao i nutritivno heterogenoj sredini obuhvataju različite tipove reverzibilne i ireverzibilne fenotipske plastičnosti, koje preko uticaja na usvajanje i raspodelu resursa utiču na osobine životne istorije i rezistentnost prema ekstremnim uslovima životne sredine. U cilju ispitivanja efekata temperature i kvaliteta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 355 publications
(681 reference statements)
0
6
0
Order By: Relevance
“…In comparison to oak leaves, locust tree leaves have higher protein and starch contents (Tzvetkova & Kolarov ; Unruh Snyder et al ; Zhang et al ) and also contain higher levels of tannins (Unruh Snyder et al ; Al‐Masri & Mardini ). In our previous study using artificial diet, the elevation of nutrient contents increased the activities of these three enzymes (Janković‐Tomanić ). In addition, the presence of enzyme inhibitors and toxins in food is known to up‐regulate digestive enzymes of herbivore insects (Chikate et al ; Gog et al ; Roy et al ).…”
Section: Mean Squares (Ms) From Three‐way Anova For Specific Activitimentioning
confidence: 81%
“…In comparison to oak leaves, locust tree leaves have higher protein and starch contents (Tzvetkova & Kolarov ; Unruh Snyder et al ; Zhang et al ) and also contain higher levels of tannins (Unruh Snyder et al ; Al‐Masri & Mardini ). In our previous study using artificial diet, the elevation of nutrient contents increased the activities of these three enzymes (Janković‐Tomanić ). In addition, the presence of enzyme inhibitors and toxins in food is known to up‐regulate digestive enzymes of herbivore insects (Chikate et al ; Gog et al ; Roy et al ).…”
Section: Mean Squares (Ms) From Three‐way Anova For Specific Activitimentioning
confidence: 81%
“…In a previous study on the gypsy moth, it was shown that older larvae invest more into antioxidant defense under stressful conditions [30]. Adaptive lower activities of total proteases in the control environment could be a postingestive homeostatic mechanism for nutrient rebalancing under the conditions of feeding on artificial diets where proteins are present in excess [14,65]. The opposite selection pattern for leucine aminopeptidase, i.e., positive selection for higher activity of leucine aminopeptidase on the control diets in both populations and on the tannin-supplemented diet in the Robinia population, implied that protease activity in regulating nutrient balance was associated with exopeptidase leucine aminopeptidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Increased activities of protease and amylase in response to Hungarian oak observed in our study possibly indicate the homoeostatic adjustment to improve the efficiency of nutrient digestion and thus contribute to their assimilation from food with lower protein and starch content. These enzymes were also induced in response to artificial diet containing a lower concentration of proteins and/or starch (Janković‐Tomanić, ). Homoeostatic adjustment at the level of digestive enzymes is described in other insect species (Clissold et al., ; Sarate et al., ) and may be the key factor that enables exploitation of different hosts.…”
Section: Discussionmentioning
confidence: 99%